In vitro regeneration protocol of Rauvolfia serpentina L. - Khan, S; Banu, TA; Akter, S; Goswami, B; Islam, M; Hani, U; Habib, A (Bangladesh Journal of Scientific and Industrial Research, 2018)
An efficient in vitro regeneration system was developed for Rauvolfia serpentina L. through direct and indirect organogenesis from nodal and leaf explants. Among the different growth regulators, MS medium supplemented with 2.0 mg/l BAP, 0.5mg/l IAA and 0.02mg/l NAA found best for the multiple shoot formation from nodal segments. In this combination 98% explants produced multiple shoots and the average number of shoots per explants is 13∙4. The frequency of callus induction and multiple shoot induction from leaves was highest 88% in MS medium supplemented with 2.0 mg/l BAP, where mean number of shoots/explants was 12.5. The highest frequency of root induction (80%) and mean number of roots/plantlets (10) were obtained on half strength of MS medium containing 0.2 mg/l IBA. The rooted plantlets were transferred for hardening following acclimatization and finally were successfully established in the field. Bangladesh J. Sci. Ind. Res.53(2), 133-138, 2018